Ground Improvement Techniques and Geosynthetics IGC 2016 Volume 2 - Thyagaraj, T.; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
The book comprises select proceedings of the 2016 annual conference of the Indian Geotechnical Society (IGC 2016), with technical papers on the theme "Ground Improvement and Geosynthetics". The papers cover a wide range of topics, including chemical modification using admixtures, microbial-induced carbonate precipitation, geopolymers, fly ash and other industrial wastes, modification using geosynthetic materials such as natural and synthetic fibers, expanded polystyrene (EPS) geofoam, prefabricated vertical drains, geosynthetic encased-granular columns and mechanical densification through sand columns. This book is a valuable reference for researchers and practicing engineers alike.
THEME 3 : GROUND IMPROVEMENT AND GEOSYNTHETICS -- Behaviourial Study on Geopolymer Column in Soil -- A Study of Parameters Influencing Efficiency of Micropile Groups -- Alteration of CBR Values in Soft Soils using Enzymatic Lime -- Factors which Influence PVD Performance in Soft Clay Consolidation -- Experimental Study of Heave Control Technique for Expansive Soil using Micropiles and Geotextile Layers -- Effect of Underground Void on the Internal Stress Distribution in Soil -- Influence of Properties of Infill Material on the Behaviour of Geocells -- Investigation of Glass Fiber Reinforcement Effect on the CBR Strength of Cohesive Soil -- Bearing Capacity of Strip Footing on Clay Soil Reinforced with Metal Strips and with Anchors -- Application of Microbial Induced Carbonate Precipitation for Soil Improvement Via Ureolysis -- Influence of Organic Content on Fly Ash Stabilisation of Clay -- Strength Behaviours of the Clayey-Silt Soil Mixed with Fly Ashand Sand -- Strength Behaviour Of Expansive Soil Treated With Quarry Dust And Ferric Chloride -- Lime Stabilization of Subgrade with Waste Sand as Partial Soil Replacement -- Assessment Of Vetiver Grass Root-Reinforcement In Strengthening The Soil -- Geotechnical Aspects of Constructions Along the Canal Embankment using Rice Husk Ash as Stabilizer -- Use of Jhama Columns as Replacement of Stone Columns -- Laboratory Study on the Performance of Geo-Synthetic Reinforced Sand Bed -- Repeated Load Response of Encapsulated Granular Trench Supported Footings on Embankments -- Re-Appraisal of Physico-Mechanical Stability of Lime Treated Soils -- Back analysis of PVD performance in Mumbai Port -- Discharge and Absorption Capacity Tests on Composite Prefabricated Vertical Drains -- Stabilization of Clay at Sunnam Cheruvu Area in Nadergul, Hyderabad using Organic Waste -- The Tensile Strength Behavior of Lime Stabilized Soft Soil with Inclusion of Plastic Fiber -- Pullout Behaviour of Geosynthetics - a Review of Laboratory Testing Techniques -- Model Study on Cyclic Loading Responses of Flexible Pavement System Laid on Expansive Subgrade -- Evaluating the Strength Characteristics of Lime and Metakaolin Stabilized Expansive Soil -- Ground Improvement using Sand Columns to Mitigate Liquefaction - a Case Study -- Stabilization of Expansive Soil with Red Mud and Lime -- California Bearing Ratio and Permeability Behaviour of Fly Ash Reinforced with Geotextiles -- Influence of Granulated Blast Furnace Slag Contents on California Bearing Ratio Value of Clay Gbfs Mixture -- Geocell Reinforced Dense Sand Bases Overlying Weak Sand Subgrades Under Repeated Loading -- Load-Settlement Behaviour of Granular Pile on Cochin Marine Clay using Recycled Aggregate -- Transmissivity of Coir Latex Composite -- Influence of Combined Vertical and Horizontal Reinforcement on Granular Piles in Soft Clays -- Effect of Ggbs and Lime on the Strength Characteristics ofBlack Cotton Soil -- Soil Improvement using Microbial: a Review -- Long Term Strength Studies on Natural Fibre Composite (N-F-C) Sheets for Use as Separator in Flexible Pavements in Terms of CBR Values -- Coefficient of Consolidation for Vertical and Radial Drainage -- Comparative Analysis of Strength Characteristics of Soil Reinforced with Coir and Polypropylene Fibers -- Geo-Engineering Properties of Sedimented Flyash Bed Stabilized by Chemical Columns -- A Short Review of Geosynthetic Granular Column Treatment of Soft Clay Soils -- Engineered Anti Erosion Works Along the Right Bank of Jiabharali River in Assam -- Static and Cyclic Properties of Eps Geofoam -- Swell Behavior of Expansive Soils with Stabilized Fly Ash Columns.
Keywords: Engineering geology; Geotechnical engineering; Buildings -- Design and construction; Geoengineering; Geotechnical Engineering and Applied Earth Sciences; Building Construction and Design